Micropropagation And The Incorporation Of Cyanobacterial Extracts On The Regeneration Of Ficus Carica Cv. Golden Orphan - Sriskanda, Dahmendra (2022)
Ficus carica L. (Moraceae) is a nutritious fruit rich in natural fibre and vitamins. The yellow fruited Golden Orphan cultivar is sweet and firm, suitable for commercialisation in Malaysia. However, conventional methods for plant propagation are less efficient, impeding commercial farming in Malaysia. The incorporation of cyanobacteria extracts in fig micropropagation has not been explored, yet alone with the nontoxic strains belonging from the genus Nostoc and Anabaena. This research aims to establish methods for the micropropagation of Golden Orphan using different plant growth regulators and cyanobacteria extracts. In vitro nodal bud explants were established in MS media with 1 mg/L BAP and induced shoots were treated with different concentrations and combinations of cytokinin (BAP, Kinetin, Thidiazuron and Zeatin) and auxins (NAA, IAA and IBA) for shoot multiplication. The induced shoots were also tested with different cyanobacteria strains namely Nostoc sp. Penang Hill (strain 1), Nostoc Antarctic (strain 2) and Anabaena sp. Penang Hill (strain 3) to evaluate explant morphogenic responses. Regenerated shoots were rooted in MS medium supplemented with auxins (NAA, IAA and IBA) and were acclimatised.